EVALUASI PERHITUNGAN VOLUME PEKERJAAN, ANGGARAN BIAYA DAN WAKTU PEMBANGUNAN STRUKTUR DENGAN METODE BIM DAN KONVENSIONAL - Mulyati, Ely; Asri Friantori, Mohammad; Firdaus (JURNAL TEKNIK UNILAK, 2025)
Cost comparison analysis using BIM concept is important to be implemented in order to find out how much influence BIM has on project costs and how effective the use of BIM is in project cost reduction to the maximum. Using BIM in a construction project can save 50% more time than using conventional methods. This is because conventional methods cannot design a building simultaneously, whereas BIM allows the users/designers to collaborate between designs that are made simultaneously, thus eliminating delayed work in the design process. One of the facilities that need to be improved is the Bus Rapid Transit shelter, where public transportation is increasing, especially in the capital city of DKI Jakarta, the number of human population is increasing, so the basic human needs for moving must also be improved. Therefore, this final project will focus on the revitalization of Transjakarta XXX Shelter XXX, which will conduct research related to cost and time using the Building Information Modeling (BIM) method with the Autodesk Revit program. Based on this, the author aims to determine the comparison of the effectiveness of using BIM and conventional methods to calculate the volume of work, cost and time budget. The research method is to conduct a literature study to obtain data that will be modeled using Autodesk software. Based on the research results, the total concrete volume shows that the conventional volume is closer to the actual, which is -5.04% or -37.90m3, while the BIM volume to the actual is -5.04% or -37.90m3 and the total reinforcement volume shows that the conventional volume is closer to the actual, which is 2.52% or -2,116.41kg, while the BIM volume to the actual is -3.15% or -2,630.59kg. Furthermore, the calculation of the total concrete cost with the actual shows that the conventional cost is closer to the actual, which is -5.04% or -Rp34,150,157.91, while the BIM cost to the actual is -5.19% or -Rp35,110,720.54, while the difference in the estimated price or total reinforcement cost with the actual shows that the conventional cost is closer to the actual, which is -2.52% or -Rp35,145,093.36, while the BIM or Revit cost to the actual is -3.15% or -Rp43,683,037.32.